"Death by a thread" – Peritonitis due to visceral perforation by a guide wire, during proximal femur osteosynthesis with DHS: A fatal case and legal implications. (April 2015) - Durão, Carlos; Barros, André; Guerreiro, Rui; Pedrosa, Frederico
Highlights: Undiagnosed surgical complications may be only patent at the autopsy. The forensic expert needs to be aware of the rare but serious occurrences of surgical procedures. Orthopaedic surgeons can learn from an open dialogue with the pathologist. The documentation is of paramount importance to learn from mistakes. In this case the initial error was not diagnosed with the patient alive. Abstract: Iatrogenic intestinal perforations in orthopaedic surgery are very rare. Reports of iatrogenic lesions caused by a guide wire during femur fracture osteosynthesis are even scarcer. There are no similar reports in recent literature. As opposed to what is normally described the lesion documented in this case report was not identified on time resulting in death by peritonitis. The forensic autopsy allowed the identification of an intestinal perforation with faecal leakage to peritoneal space in association with a vesical perforation enabling the reproduction of the guide wire path. In view of the increasing number of osteosynthesis it is essential for the surgeon to be aware of possible complications due to guide wire perforations. Cases like this go unnoticed if the forensic pathologist is not familiarized with the surgical technique which may explain the rarity of such descriptions in literature.